2000
DOI: 10.1300/j079v26n03_01
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Economic Adaptation of Iraqi Adult Male Refugees

Abstract: This study examines the psychological and economic adaptation of Iraqi refugees, one of the increasing number of refugee groups resettling to this country in the 90s. Data were obtained from 105 Iraqi male refugees. The results revealed that Iraqi male refugees were struggling to resettle psychologically and economically in this country. The regression analyses confirmed that predictor variables (including social support, education level, and motivation for migration) significantly explained the variances in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 45 publications
2
29
0
2
Order By: Relevance
“…Our research is consistent with previous findings that suggest refugees fare worse when it comes to employability in the host country irrespective of their professional skills (Tabeka, 2000; Bloch, 2002b). Although prior studies have reported similar findings, they have used appropriate comparison groups in their research design such as comparing the refugees with a group similar in culture, language, and country of origin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our research is consistent with previous findings that suggest refugees fare worse when it comes to employability in the host country irrespective of their professional skills (Tabeka, 2000; Bloch, 2002b). Although prior studies have reported similar findings, they have used appropriate comparison groups in their research design such as comparing the refugees with a group similar in culture, language, and country of origin.…”
Section: Discussionsupporting
confidence: 93%
“…Unemployment and underemployment affects refugees worldwide (Bloch, 2002a; Bloch, 2000b; Tabeka, 2000; Owen et al, 2000; Twomey, 2001). Although research focuses on post-displacement factors in refugee integration, little investigates post-displacement employment outcomes and its implication for health and well being.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, Breslow and colleagues (1997) and Ives (2005Ives ( , 2007 found sponsorship vital to refugee resettlement outcomes: refugees who had congregation-affiliated sponsors had greater opportunities for upward mobility, higher-than-minimum-wage income, and employment benefits such as adequate health care coverage and retirement plans. Resettlement research examining refugee employment in Canada (e.g., Krahn, Derwing, Mulder & Wilkinson, 2000), Italy (Korac, 2003), the UK (Duke, 1996), and the United States (Ives, 2005(Ives, , 2007Takeda, 2000) indicates that unless there is some mediation, most refugees who arrive with little to no English proficiency will end up in no-or low-skill, low-wage labor from which there is little upward mobility.…”
Section: Congregational Participation In Contextmentioning
confidence: 99%
“…Within this more recent group were many families who were directly or indirectly (i.e., vicariously) affected by wartime traumas including torture and executions. Research studies have shown a high rate of depression, anxiety, and post-traumatic stress disorder in this more recent group of immigrants from Iraq (e.g., Jamil et al, 2002;Jamil, Nassar-McMillan, & Lambert, 2004;Jamil, Nassar-McMillan, Salman, Tahar, & Jamil, 2006;Takeda, 2000). Treatment strategies include a multidisciplinary wraparound approach that provides a variety of diverse services to support the affected families and manage the symptoms (Kira, 2002).…”
Section: Arab Muslim Lebanese Palestinian and Iraqi/chaldean Amerimentioning
confidence: 99%